К вопросу о минимизации числа межслойных переходов при трассировке печатных плат - Luzin, S. Yu.; Petrosjan, G. S.; Polubasov, O. B. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
Approaches to the problem of minimizing the number of interlayer transitions on a printed circuit board are considered. Methods are proposed for reducing the number of interlayer transitions by connecting to a transition associated with a contact or a branching point of conductors. Traditional methods that reduce the number of transitions on conductors by changing the layer of their segments do not take this possibility into account.